A framework for learning objects reusability within learning activities - Sampson, Demetrios; Papanikou, C. (2009)
Over the last decade Learning Objects (LOs) have gained a lot of attention as the basis for creating and handling educational digital content in technologyenhanced learning. The main advantage of LOs is considered to be their potential for component-based reusability in different learning settings. However, despite the importance of the concept of reusability and its potential benefits in educational content production and deployment, there is not a consistent framework for LOs reusability that would allow organizations to assess the conditions and eventually implement systematic LOs reuse. This is a drawback in adopting the LOs paradigm towards reducing costs and effort, while maintaining high quality. In this paper, we study the process of reusing LOs within the context of a technology-enhanced learning activities design and development and propose a consistent framework for LOs reusability which has been already adopted in various European Initiatives in the field. © 2009 IEEE.